A Systematic Review Study by Comparing the Effects of Leucoreduction of Blood Components Using Pre-Storage Filters and Post-Storage Filters on Clinical Outcomes - Yogesh Agrawal; Sunita Bundas; Naveen Khanna (Journal of Biomedical and Pharmaceutical Research, 2023)
Background: Transfusion therapy is an effective treatment method but comes with inherent risks such as transfusion reactions, infection transmission, alloimmunization, and platelet refractoriness. Leukocyte reduction, achieved through apheresis or pre- or post-storage filtration, aims to mitigate these risks and potentially reduce the need for antibiotics and hospital stays. Methods: To conduct this systematic review, comprehensive searches were performed using databases such as MEDLINE (PubMed), CINAHL (EBSCO), PsycINFO, Scopus, The Cochrane Library, Web of Science Core Collection, Embase, and LILACS. Grey literature sources were also utilized. Two independent reviewers screened titles and abstracts, and critical appraisal of selected papers was conducted using JBI tools. Relevant data for the review question was extracted using JBI SUMARI. If feasible, a risk analysis of publication bias, meta-analysis, and narrative synthesis were performed. Results: The results of the systematic review will provide insights into the comparative effectiveness of post-storage filters and pre-storage filters in leukocyte reduction during transfusion. Clinical outcomes such as transfusion reactions, bacterial infection, length of hospital stay, and mortality will be assessed. Meta-analyses and narrative synthesis will be utilized to present the findings. The certainty of evidence will be evaluated using the GRADE approach, and a Summary of Findings will be provided, including absolute risks for the pre-storage filter group and the post-storage filter group. Conclusion: This systematic review aims to inform clinical decision-making and guide future research in transfusion medicine. By analyzing methodologically sound studies and employing appropriate meta-analyses, the review will identify the optimal approach for reducing transfusion-related complications and improving patient outcomes. The results will be disseminated through publication in a peer-reviewed journal and presented at conferences and professional meetings. Keywords: Clinical outcomes, leukocyte reduction, post-storage filter, pre-storage filter, transfusion.